How immune breakthroughs could slow disease progression and improve prognosis in COVID-19 patients: a retrospective study - Wang, Yiting; Zhao, Bennan; Zhang, Xinyi; Zhang, Xia; Gao, Fengjiao; Yuan, Xiaoyan; Ren, Xiaoxia; Li, Maoquan; Liu, Dafeng (Frontiers in Immunology, 2023)
Background: Previous infections and vaccinations have produced preexisting immunity, which differs from primary infection in the organism immune response and may lead to different disease severities and prognoses when reinfected. Objectives: The purpose of this retrospective cohort study was to investigate the impact of immune breakthroughs on disease progression and prognosis in patients with COVID-19. Methods: A retrospective cohort study was conducted on 1513 COVID-19 patients in Chengdu Public Health Clinical Medical Center from January 2020 to November 2022. All patients were divided into the no immunity group (primary infection and unvaccinated, n=1102) and the immune breakthrough group (previous infection or vaccination, n=411). The immune breakthrough group was further divided into the natural immunity subgroup (n=73), the acquired immunity subgroup (n=322) and the mixed immunity subgroup (n=16). Results: The immune breakthrough rate was 27.16%. In the no immunity group, the severe rate and the mortality rate were all higher, and the coronavirus negative conversion time was longer than those in the immune breakthrough group. In addition, in the no immunity group, although lymphocyte counts and T subsets at admission were higher, all of them decreased consistently and significantly and were significantly lower than those in the immune breakthrough group at the same time from the first week to the fourth week after admission. The total antibody levels and specific Immunoglobulin G (IgG) levels increased gradually and were always significantly lower than those in the immune breakthrough group at the same time from admission to the fourth week after admission (all p<0.001). Moreover, in the natural immunity subgroup, lymphocyte counts and T subsets at admission were the highest, and total antibody levels and specific IgG levels at admission were the lowest. Then, all of them decreased significantly and were the lowest among the three subgroups at the same time from admission to one month after admission.